Magnesium and zinc cation distributions and correlation with curie temperature in some LiTaO3-based ferroelectric ceramics - 주기태; Jean Ravez; Paul Hagenmuller; J. Senegas (ACADEMIC PRESS, 1987)
Nonstoichiometric ferroelectric ceramics based on LiTaO